Association between hand grip strength and health-related quality of life among Malaysian middle-aged adults - Shun, Qian Kang; Harith, Sakinah; Ying, Qian Ong; Mohd Yusof, Barakatun Nisak (Human Resource Management Academic Research Society, 2021)
In September 2019, the Deputy Prime Minister of Malaysia announced the government’s commitment to legislate an Act to sustain and improve the health-related quality of life (HRQoL) of the elderly. HRQoL refers to the perceived physical and mental health of an individual or a group over time. Hand grip strength (HGS) is an indicator for mobility limitation and HRQoL. This cross-sectional study was performed to examine the association between HGS and HRQoL among 106 adults aged from 30 to 60 years in Universiti Sultan Zainal Abidin (UniSZA), Terengganu. Out of the total sample, 37.7% of respondents were males, and 62.3% were females. The mean age of respondents was 38.44 (7.78) years. Sociodemographic characteristics, anthropometric measurements (weight, height, HGS), protein intake, physical activity (PA) level and HRQoL were assessed. The prevalence of respondents to have normal right HGS was 79.2%, and normal left HGS was 69.8%. The respondents were classified as healthy and unhealthy according to the EQ-5D-5L index score. The prevalence of the healthy group was 67.9%. A significant difference was only found in HGS, protein intake and PA between genders, while a significant association was only found between HGS and PA with HRQoL. The results revealed that HGS is linked with HRQoL, whereas low HGS is related to the impaired status of HRQoL by EQ-5D-5L index score and visual analogue scale (VAS) score in Malaysian males and females. More investigation is warranted to examine the specific plausibility between HGS and HRQoL.